Pengaruh penerapan sistem closed list dan penambahan jenis pajak daerah terhadap upaya pemungutan pajak daerah - Noviyanti Noviyanti; Fauziah Zen (Indonesian Treasury Review: Jurnal Perbendaharaan, Keuangan Negara dan Kebijakan Publik, 2022)
This study investigates the effect of the closed list system and the new tax assignment stipulated in Law 28/2009 on local tax efforts in Indonesia. It also examines the other influential factors affecting local tax efforts. The local tax effort is a ratio of the actual (collected) local tax revenue to its potential tax capacity. A random-effect regression model is applied to the province's tax effort analysis, while a fixed-effect regression model is applied to the municipalities' tax effort analysis. The dataset consists of local budget and socio-economic indicators of 31 provinces and 372 municipalities in Indonesia during 2005-2019. The results show that the closed-list system has a negative impact on municipalities' tax efforts, while the new tax assignment in Law 28/2009 positively affects both provinces and municipalities. This study also finds other influential factors on local tax efforts. Block grant positively affects the municipality's tax effort, while categorical grant negatively affects the province's tax effort. Additionally, population density positively affects the province's tax efforts, but the results of audited subnational financial reports only affect the municipality's tax efforts. Municipality's tax effort is also affected by urban area factors.